Estudo sobre o desempenho de válvulas não-mecânicas como alimentadores de biomassa residual de borra de café em reatores de leito pneumático circulante: experimentação e modelagem via CFD-TFM - Sousa, Lucas Massaro (Universidade Federal de São Carlos, 2020)
The continuous and stable feeding of particulate solids to reactors is essential for energy cogeneration in industrial processes, for example, by using biomass residues. Nevertheless, flow instabilities and blockage of mechanical feeder’s moving parts are commonly reported with these materials, which jeopardizes the process’ performance, automation, and safety. This study is aimed at evaluating the performance of non-mechanical devices (an L-valve and a spouted bed) to promote the feeding of spent coffee grounds to circulating fluidized bed (CFB) units. The physical and flow properties were determined for dry spent coffee grounds with mean sizes between 225 and 550 μm, as well as for samples with moisture content up to 60%. Some of the properties determined were the true, apparent, and bulk densities, minimum fluidization velocity, Hausner ratio, static and dynamic repose angle, and effective internal friction angle. Then, feeding experiments using both feeders were carried out at pilot-scale CFB reactors (riser diameter and height of 21 mm and 2 m), available at the Drying Center/UFSCar. The fluid dynamics of the systems with spent coffee grounds was assessed by pressure and solids flowrate (Ws) measurements under different operating conditions, such as different air flowrates in the riser and feeder, as well as with different distances between the riser and air inlets with the spouted bed. The solids flowrate with the L-valve lies between 0.6 and 10.0 g/s, while it ranges from 1.2 to 11.0 g/s with the spouted bed feeder. The pressure measured at the feeders and Ws were accurately related by linear equations. The feeders’ performance was related to the samples’ properties, then flow instabilities and lower values of Ws were observed for samples with poorer flowability. Overall, the spouted bed exhibited improved performance and flexibility than the L-valve in handling dry and wet spent coffee grounds to the CFB unit. The experimental data was used to validate simulations based on computational fluid dynamics with the Two-Fluid model (TFM) approach. The difference between experimental and simulated solids flowrate was less than 20% for different operating conditions with the feeders. From the validated TFM simulations, details on the gas-solid flow dynamics in the feeders and riser were verified by means of volume fraction contours, and velocity vectors for gas and solid phases. Finally, new operating conditions and different feeder and riser geometries were numerically investigated for the spouted bed feeder, and the maximum solid flowrate could be increased from 11 to 30 g/s. The simulations proved to be reliable and cost-effective tools to optimize spent coffee grounds handling or to implement the feeders in larger-scale commercial applications.
On the performance of non-mechanical valves for feeding spent coffee grounds into circulating fluidized bed reactors: experimental analysis and CFD-TFM simulation
Keywords: Biomassa; Alimentadores de sólidos; Transporte pneumático; Borra de café; Válvula-L; Leito de jorro; Reator; CFD; Modelo duplo-fluido; Biomass; Solid feeder; Pneumatic transport; Spent coffee ground; L-valve; Spouted bed; Reactor; Two-fluid model; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA